Premature ovarian insufficiency: a syndrome or diagnosis - Т. Ф Татарчук; Н. В. Косей; Т. Н. Тутченко (Publishing House TRILIST, 2017)
The article presents modern views on the etiology, pathogenesis, diagnosis and management of premature ovarian insufficiency (POI) - syndrome which is heterogeneous in the etiology and pathogenesis and has a significant negative impact not only on the reproductive sphere, but also on the quality of life, the overall morbidity and mortality of women. The term "premature ovarian insufficiency" is used today by leading professional societies in the US and Europe and is recommended for use in clinical practice. In the clinical recommendations of 2016, the European Society for Human Reproductology and Embryology provides the following definition of the POI - the clinical syndrome whose main manifestation is the cessation of ovarian function before the age of 40, which is characterized by a disruption of menstrual function, an increase in gonadotropins and a decrease in the concentration of estradiol. Given the already well-formed trend in developed countries for the late realization of reproductive function, a higher frequency of POI in a group of women of late reproductive age is an actual problem of modern reproductive technology. The clinical significance of the POI goes beyond gynecology: prolonged hypoestrogenia is accompanied by a decrease in bone density, the disease also has negatively affects the incidence of cardiovascular and neurological diseases, cognitive function, sex life and the social realization of women. Hormone replacement therapy is an obligatory and essential component of correction of symptoms and prevention of long-term consequences of estrogen deficiency. With this in mind, the article discusses in detail the effects and safety issues of the application of various types and ways of hormone replacement therapy available today for the elimination of symptoms of estrogen deficiency and the prevention of its consequences in women with POI and various concomitant conditions. The pharmacological effects of natural transdermal estrogens and micronized progesterone make it possible to treat this combination as the most optimal variant of hormone replacement therapy for women with POI due to the flexible dosage regimen that allows to provide individual needs for compensation of estrogen deficiency.